Diverting Enterostomy Improves Overall Survival of Patients With Severe Steroid-refractory Gastrointestinal Acute Graft-Versus-Host Disease. Issue 5 (November 2021) - Khodr, Justine; Zerbib, Philippe; Rogosnitzky, Moshe; Magro, Leonardo; Truant, Stéphanie; Yakoub-Agha, Ibrahim; Duhamel, Alain; Seguy, David
Abstract : Objective: The aim of this study was to evaluate the benefit of diverting enterostomy (DE) in patients with severe steroid-refractory (SR) gastrointestinal acute graft-versus-host-disease (GI-aGVHD) following allogeneic hematopoietic stem-cell transplantation (ASCT). Summary and Background Data: Severe GI-aGVHD refractory to the first-line steroid therapy is a rare but dramatic life-threatening complication. Second lines of immunosuppressors have limited effects and increase the risk of sepsis. Data suggest that limiting GI bacterial translocation by DE could restrain severe GI-aGVHD. Methods: From 2004 to 2018, we retrospectively reviewed all consecutive patients undergoing ASCT for hematologic malignancies who developed severe SR GI-aGVHD. We compared patients in whom a proximal DE was performed (Enterostomy group) with those not subjected to DE (Medical group). The primary endpoint was the 1-year overall survival (OS) measured from the onset of GI-aGVHD. Secondary endpoints were the 2-year OS and causes of death. Results: Of the 1295 patients who underwent ASCT, 51 patients with severe SR GI-aGVHD were analyzed (13 in Enterostomy group and 38 in Medical group). Characteristics of patients, transplantation modalities, and aGVHD severity were similar in both groups. The 1-year OS was better after DE (54% vs 5%, P = 0.0004). The 2-year OS was also better in "Enterostomy group" (31% vs 2.5%; P = 0.0015), with a trend to lower death by sepsis (30.8% vs 57.9%; P = 0.091). Conclusion: DE should be considered for severe GI-aGVHD as soon as resistance to the corticosteroid is identified.